OPTIMIZATION AND BENCHMARKING OF THE ANTIOXIDANT ACTIVITY OF ATHRIXIA PHYLICOIDES EXTRACTS - De Beer, D.; Joubert, E. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Athrixia phylicoides (Asteraceae), commonly known as bush tea and used as herbal tea or medicinal drink, is currently being considered for commercialization. The opportunity also exists to exploit bush tea for the food additive and nutraceutical markets. Against this background, the antioxidant activity of bush tea aqueous dried extracts (DEs) was evaluated using several test systems and benchmarked against several commercial DEs from fermented and unfermented rooibos (Aspalathus linearis) and honeybush (Cyclopia spp.) teas. The major phenolic compounds in bush tea DEs were tentatively identified. Optimization of the extraction procedure, in terms of solvent, temperature and time, was performed to obtain an extract with high antioxidant activity and content of the major bush tea phenolic compounds. The antioxidant activity of bush tea DEs in free radical scavenging, iron reducing and lipid peroxidation assays was similar to that of commercial honeybush extracts. However, antioxidant activity of bush tea DEs was slightly less than that of commercial fermented rooibos DEs, but substantially lower than that of unfermented rooibos DEs. The major phenolic compounds in bush tea DEs are phenolic acids, especially caffeic acid derivatives. A unique compound, namely 5-hydroxy-6,7,8,3’,4’,5’-hexamethoxyflavon-3-ol, was also detected in some extracts. The optimized extraction procedure entails extraction with 50% ethanol at 50ÂºC for 20 min using a 50:3 volume to mass ratio. Extraction optimization gave an extract with antioxidant potential similar to fermented commercial rooibos DEs and one of the unfermented rooibos DEs. Further work is needed to identify compounds responsible for antioxidant activity of bush tea DEs. Acknowledgements: National Department of Agriculture, South Africa, provided funding